1981
DOI: 10.1128/jvi.38.1.125-135.1981
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the provirus within NIH 3T3 cells transfected with Harvey sarcoma virus DNA

Abstract: NIH 3T3 cells transformed with unintegrated Harvey sarcoma virus (HSV) linear DNA generally acquired a complete HSV provirus. Infection of these transformed cells with Moloney murine leukemia helper virus was followed by release of infectious particles. The HSV provirus within these transfected cells was convalently joined to nonviral DNA sequences and was terned "cell-linked" HSV DNA. The association of this cell-virus DNA sequence with the chromosomal DNA of a transfected cell was unclear. NIH 3T3 cells coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1981
1981
1993
1993

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
(52 reference statements)
1
11
0
Order By: Relevance
“…38, 1981 cells lacks the right end of the HSV provirus (corresponding to the 3' end of the viral RNA), we concluded that the transforming gene of HSV is located in the central or left-end portion of the HSV provirus (corresponding to the middle or 5' end of the viral RNA). We also concluded that the inefficient transmissibility of these deleted viral genomes was probably correlated with the absence of the right end of the provirus (16). Such a conclusion is consistent with the findings of others that indicate the vital role of 3'-proximal RNA sequences in several steps of viral DNA synthesis (13).…”
supporting
confidence: 91%
See 3 more Smart Citations
“…38, 1981 cells lacks the right end of the HSV provirus (corresponding to the 3' end of the viral RNA), we concluded that the transforming gene of HSV is located in the central or left-end portion of the HSV provirus (corresponding to the middle or 5' end of the viral RNA). We also concluded that the inefficient transmissibility of these deleted viral genomes was probably correlated with the absence of the right end of the provirus (16). Such a conclusion is consistent with the findings of others that indicate the vital role of 3'-proximal RNA sequences in several steps of viral DNA synthesis (13).…”
supporting
confidence: 91%
“…Polyadenylated cytoplasmic RNA was prepared from three transformed cell lines (clones Xl, 16-1, and 16-7), each of which carried a delHSV genome. In addition, as control reagents, we prepared RNAs from two transformants which bore complete HSV proviruses (clones 14 and 16) (16). The RNA samples were subjected to agarose gel electrophoresis in the presence of methylmercuric hydroxide, and the RNA contents of the gel were transferred and affixed to diazo-derivatized filter paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the number of new bands seen indicated directly the number of distinguishable copies of the A-MuLV genome introduced into the cells. The very high intensity of hybridization seen suggested that the new DNA was present at an amplified level of 5 to 10 copies per cell, as has been observed for other transfected DNAs (12). Cleavage with the enzyme XbaI suggested that these new A-MuLV DNAs were not the result of conventional viral infection.…”
Section: Resultsmentioning
confidence: 51%